Perancangan Alat Bantu Perakitan Spring Bed yang Ergonomi Berdasarkan Analisa RULA dan REBA - Anwardi, Anwardi; Nofirza, Nofirza; Vilhelmina, Vira; Anggraini, Wresni; Silvia, Silvia (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 7 No 1 (2021): Volume 7 N0 1 June 2021DO - 10.24843/JEI.2021.v07.i01.p10, 2021)
CV. XYZis an industry engaged in the field of furniture producing spring bed, cabinets, buffets, chairs and others. At the spring bed assembly station, the worker assembles a springbed frame on the floor with a work position bent, squatting or sitting up to form a working posture with angles of 45 0 to 70 0 and does not use tools to support ergonomic position and posture. The purpose of this study was to design an ergonomic tool s for conduct ed work activities on the skeleton spring bed assembly station us e the RULA-REBA method s . The method of research is done by compar ed scores and levels before and after assembly tool design. The results show that REBA score is at 9/11 level and RULA is at 7/7 level which means that the current working condition must be improved and very unsafe for workers. After assembling the assembly tool us e SolidWork software with dimension size is determined based on anthropometry data, where the height is 102 cm, length 204 cm, and width 134 cm. Then simulated us e ErgoFellow 2.0 software, obtained REBA 4 and 5 score from 11 total level and RULA score is 3/7 level which means the risk of injury to worker in assembly station of skeleton of springbed can be minimized.